POLITICAL CRISIS AND SOCIAL PROTEST IN THAILAND - E. V. Koldunova (MGIMO University Press, 2015)
The article focuses on socio-political activism, main features of socio-political contradictions and the couses of the recent social protests in Thailand. Thailand has the longest democratic tradition among ther countries of South-east Asia. Yetbackin 1932 the country has changed the absoulute monarchy to a constitutional one. However in the XXth century Thailand had lived through more than five decades of authoritarianism. The number of military coupd'etats which took place in Thailand now equals to almost twenty. At the same time, despite such a long authoritarian rule the country witnessed the formation of various elements of civil society. In the second part of the XX century the student protests of 1973–1976 became the most vivid example of civic activism. The social protest in Thailand reached its most active phase in the first decade of this century when the country splitted into two camps – one of thes-o-called «Red Shirts» and Another One of the «Yellow Shirts». The «Red Shirts» supported billionere Thaksin Shinawatra, a Prime Minister of Thaialnd in 2001–2006. The «Yellow Shirts» opposed him. Thet women tioned camps created new social movements – «People's Alliance for Democracy» («Yellow Shirts») and «United Front for Democracy against Dictatorship» («Red Shirts»). Since 2006 Thailand has seen several stages of the development of the social protest. The most recent one starte din November 2013 and end edin May 2014 when after more than half a year of mass meetings in the country's capital Bangkok the military took power again.